Comparative community structure of archaea in rumen of buffaloes and cattle. (30th December 2016) - Paul, Shyam S; Dey, Avijit; Baro, Daoharu; Punia, Balbir S
Abstract: BACKGROUND: Detailed knowledge of the community structure of methanogens is essential for amelioration of methane emission from livestock species. Several studies have indicated that predominant methanogens of buffalo rumen are different from those in cattle. However, predominant genera of methanogens reported by individual studies varied primarily because of limited scope of sampling, sequencing of limited number of sequences and potential PCR bias in individual studies. In this study, the collective comparative diversity of methanogenic archaea in the rumen of cattle and buffaloes was examined by performing a meta‐analysis of all the 16S rRNA (rrn) sequences deposited in GenBank. RESULTS: Ruminal methanogen sequences of buffalo were clustered into 900 species‐level operational taxonomic units (OTUs), and ruminal methanogen sequences of cattle were clustered into 1522 species level OTUs. The number of species‐level OTUs shared between cattle and buffaloes was 229 (10.4% of all OTUs), comprising 1746 sequences (27% of the total 6447 sequences). According to taxonomic classification by three different classifiers, Methanobrevibacter was found to be the most predominant genus both in cattle (69–71% of sequences) as well as buffaloes (65.1–68.9% of sequences). Percentage of Methanomicrobium was much higher ( P  < 0.05) in the case of buffalo (18%) than that of cattle (4.5%). On the other hand, percentages of Methanosphaera ‐ and Methanomassiliicoccus ‐like methanogens were much higher ( P  < 0.05) in cattle than in buffaloes. CONCLUSION: This study indicated that there is a substantial difference in community structure of ruminal methanogens of cattle and buffaloes. The study has also indicated that the percent of species‐level operational taxonomic units shared between cattle and buffalo is very low, and thus host species‐specific methane mitigation strategies need to be developed for cattle and buffaloes. © 2016 Society of Chemical Industry